Analysis of the Influence of Tourism Indicators on Local Revenue in the Regency/City of Bali Province - Putri, Made Anandhita Mahisa; Dewi, Made Heny Urmila (Business and Investment Review, 2025)
This study aims to analyze the effect of the number of tourist visits, the number of tourist attractions, and hotel restaurant taxes simultaneously and partially on local revenue in the Regency/City of Bali Province. The data used in this study are secondary data, namely by observing related documents or data sources. The population used in this study is the total number of tourist visits, the number of tourist attractions, hotel restaurant taxes, and local revenue in the Regency/City of Bali Province, with the number of samples used being in a six-year period, namely 2018 - 2023. The analysis technique used is panel data regression. The results of the study indicate that the number of tourist visits, the number of tourist attractions, and hotel restaurant taxes simultaneously affect the local revenue of the Regency/City in Bali Province. The number of tourist visits partially has a positive and insignificant effect on local revenue in the Regency/City of Bali Province, the number of tourist attractions, and hotel restaurant taxes partially have a positive and significant effect on local revenue in the Regency/City of Bali Province.